Annals of Palliative Medicine is indexed in PubMed - Simone II, Charles B. (Annals of Palliative Medicine; Vol 4, No 2 (April 30, 2015): Annals of Palliative Medicine, 2015)
We are excited to pass along the great news that Annals of Palliative Medicine (APM) will now be fully indexed in PubMed/MEDLINE. All accepted articles of future issues of APM will be indexed and available on PubMed, and all previously published APM articles will also be searchable in PubMed as soon as the indexation process is finished, which is expected to be completed within the month.